The spirit of the Constitution John Marshall and the 200-year odyssey of McCulloch v. Maryland - Schwartz, David S. ca. 20./21. Jh (Oxford scholarship online, 2019)
'The Spirit of the Constitution' covers the impact and reputation of both McCulloch and Justice Marshall himself throughout American history. One of the central threads of American history is the battle over the proper reach of the federal government's power, and that story cannot be told without reference to McCulloch. Schwartz's analysis of the shifting interpretations of McCulloch and Marshall over the course of American history not only reaffirms the case's importance, it also helps us understand the circuitous process by which American constitutional law and ideology are made